“Not a Church Anymore”: The Deconsecration and Conversion of the Dominican Church in Münster (Westphalia, Germany) - Radermacher, Martin (Material religion, 2021)
This article studies the ways in which communicative attributions change when a church building, in this case the Dominican Church in Münster (Westphalia, Germany) is converted from a place of religious ritual to a place which exhibits art. The Dominican Church was deconsecrated in November 2017 and, since June 2018, houses an art installation by Gerhard Richter: a Foucault Pendulum. The observation and analysis of this process of deconsecration and conversion demonstrates, first, how the physical built structure is embedded in different kinds of communication (e.g. religion, art, politics, economics). Second, this study focuses on the agency of socio-spatial arrangements which afford specific kinds of communication. In this regard, I introduce the concept of “atmosphere” to analytically grasp the semantic agency of a given architectural setting in its entanglement with social communication.